SOCIAL LIFE OF NORTHEAST INDIA AS DEPICTED IN HINDI FICTION - Shrivastava, Pooja; Singh, Manoj Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The title of this research is 'Social life of Northeast India as depicted in Hindi fiction'. As we know that Indian society is a collection of different communities. This means that this society is made up of many communities. For years, many communities have been living together lovingly and living their lives. In this Indian society, there are some communities or classes which have been neglected, despised, deprived and exploited for years. Among them, 'Adivasis' is an important community. In this study, the social system, social problems etc. of Northeast India have been divided into some points and analyzed. The researcher has found that at present, the study and teaching of the tribal society of the Northeast is being done under different disciplines. Due to which, a lot of information is being obtained about the tribal life-philosophy and values. But as far as Hindi language and literature is concerned, Northeast India has remained forgotten by the writers. It can be said in this way that from the point of view of Hindi literature writing, Northeast India has always been neglected and untouched. Along with this, it is also true that tribal life has been even more absent in Hindi literature writing. While doing research work, it has been found that actually writing about Northeast India has started in the twenty-first century. Tribal life has emerged in these works. In fiction literature, the question of tribal identity and existence of Northeast India has been mainly raised. Along with this, the main concerns and problems of the tribal society of Northeast India have been expressed.